Magnetic nanocomposites based on poly(styrene-b-butadiene-b-methyl methacrylate) and modified Fe2O3 nanoparticles. (May 2016) - Barandiaran, I.; Kortaberria, G.
Graphical abstract: Highlights: PS and PMMA brushes were anchored to nanoparticle surface by grafting from technique. Functionalized nanoparticles were dispersed and selectively placed at desired domain. Lamellar morphology of triblock copolymer was maintained with nanoparticle addition. Nanocomposites take properties of nanoparticles, showing superparamagnetic behavior. Abstract: In this work an ABC-type triblock copolymer has been used to prepare magnetic organic/inorganic nanocomposites by selectively placing maghemite nanoparticles modified on their surface with different polymer brushes. As ABC-type triblock copolymers can be nanostructured resulting in different morphologies with three different nano-sized block domains, they constitute interesting templates for selectively host nanofillers on them. In this work magnetic nanoparticles have been surface-modified with polystyrene and poly(methyl methacrylate) brushes following the grafting through method, in order to selectively place at polystyrene and poly(methyl methacrylate) block domains of the nanostructured block copolymer. Morphological characterization of ABC-type copolymers presents a higher complexity than that of AB diblock or ABA-type triblock copolymers, as a higher amount of parameters controlling the nanostructuring process must be taken into consideration, especially the interaction parameters between blocks that are of crucial importance, besides block composition and solvent employed for film preparation. Morphology of neat block copolymer and nanocomposites with polystyrene- and poly(methyl methacrylate)-modified nanoparticles has been analyzed by atomic force microscopy. Nanocomposites maintained the lamellar nanostructure of poly(styrene- b -butadiene- b -methyl methacrylate) triblock copolymer, with nanoparticles selectively placed into the desired domains, as it has been demonstrated by both AFM and DSC measurements. Magnetic characterization by vibrating sample magnetometry demonstrates that magnetic properties of nanoparticles have been successfully transferred to nanocomposites.